Is estrogen exposure a protective factor for pancreatic neuroendocrine tumours in female patients with multiple endocrine neoplasia syndrome type 1?. (6th April 2017) - Qiu, Wei; Christakis, Ioannis; Stewart, Ashley A.; Vodopivec, Danica M.; Silva‐Figueroa, Angelica; Chen, Huiqin; Woodard, Terri L.; Halperin, Daniel M.; Lee, Jeffrey E.; Yao, James C.; Perrier, Nancy D.
Summary: Objective: Pancreatic neuroendocrine tumours (PNETs) are the most common cause of death in patients with multiple endocrine neoplasia type 1 (MEN1). Women have been shown to have improved survival, which may suggest a possible protective effect of female sex hormones. The aim of this study was to evaluate the relationship between estrogen exposure and PNET tumourigenesis, tumour growth and survival in female MEN1 patients with these tumours. Design: We performed a retrospective chart review of the existing MEN1 database in our institution. Detailed information about female patients' menstrual and reproductive history, and PNET clinicopathologic characteristics was collected. Questionnaires regarding estrogen exposure were used to collect information that was missing in the database. Patients: Of 293 confirmed MEN1 cases, 141 women met the inclusion criteria. Measurements: We used measures of cumulative estrogen exposure time (CEET), parity, live birth pregnancies and bilateral oophorectomy to estimate estrogen exposure. Results: There was no significant association between CEET and time to PNET diagnosis (hazard ratio = 0·966, P  = 0·380). For the correlation between estrogen exposure and PNET type, size, numbers, distant metastasis, lymph node metastasis, lymphovascular invasion, AJCC (American Joint Committee on Cancer) stage and overall survival, only CEET was significantly correlated with PNET size ( P  = 0·043). Conclusions: In female patients with MEN1, estrogen exposure may inhibit PNET growth. A demonstrable protective effect against PNET tumourigenesis, tumour growth and survival of patients with these tumours may require a larger cohort.